John Fransham, the Norwich Polytheist: An English Pagan In The Eighteenth Century - Wheeler, Graham John (The journal of religious history, literature and culture, 2020)
This article seeks to shed new light on an unresolved question in modern religious history: how did classical traditions of paganism come to be revived in modern times in the form of neo-paganism? It seeks to contribute to addressing this question by identifying a hitherto overlooked individual who embraced revived paganism as a religious philosophy before other, better known figures who have been discussed by previous scholars. The individual in question was the teacher and writer John Fransham (1730-1810). This article seeks to elucidate the main tenets of Fransham's religious outlook and to locate him within the intellectual context of his time, as both a product of and a rebel against the British Enlightenment. It also publishes his most explicitly pagan piece of writing for the first time.